ANALISIS FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP PEMILIHAN METODE PENILAIAN PERSEDIAAN (Studi Kasus Pada Perusahaan Dagang Dan Manufaktur Yang Terdaftar Di BEI Tahun 2008-2012) - Brian Syailendra; Rahardja Rahardja (Diponegoro Journal of Accounting, 2014)
The research aims to analyze the selection that influence a company's decision to use the methods of inventory valuation in its financial statements. The research examines five independent variables were it tested, inventory variability, company size, inventory intensity, ownership structure, and Accounting earnings variability. While the dependent variable, namely the FIFO method of inventory valuation and Average.The population in this research is a trading and manufacturing company listed on the Indonesian stock exchange years between 2008-2012. The selected sample is a company that consistently over the period of observation using only one method of inventory valuation. This research uses non-random purposive sampling method to determine the sample. Data analysis was performed using SPSS version 17Results of the research are: (1) inventory variability significantly influence the selection of inventory valuation methods, (2) the amount of the company significantly influence the selection of inventory valuation methods, (3) the intensity had no effect on the selection of supplies inventory valuation method, (4 ) ownership structure significantly influence the selection of inventory valuation methods, (5) accounting earnings variability has no effect on the selection method of inventory valuation.